Efficacy and Safety of Endovascular Treatment for Acute Large-Vessel Ischemic Stroke Beyond 6 h After Symptom Onset: A Meta-Analysis - Zhongxing, Ye; Zhiqiang, Liu; Jiangjie, Wang; Qing, Chen; Jinfeng, Zhang; Chaoqun, Weng; Feng, Li (Frontiers in Neurology, 2021)
Background: Overwhelming evidence demonstrated benefit from endovascular thrombectomy (EVT) for acute ischemic stroke (AIS) within 6 h after symptom onset. However, uncertainties remain about the situation beyond 6 h after symptom onset. Here we performed a meta-analysis to pooled assess the efficacy and safety of EVT for AIS more than 6 h after symptom onset. Methods: We searched PubMed, EMBASE and Chinese Biomedical (CBM) through July 2019. Studies of early (≤ 6h) versus delay (> 6h) EVT in AIS patients who were selected with radiological evaluation criteria were included. The rates of functional independence, successful recanalization, mortality and symptomatic intracranial hemorrhage (sICH) were used for assessment. Results: 8 eligible articles were included in the meta-analysis, 3265 patients underwent early EVT, 1078 patients received delayed EVT. Patients treated with early EVT showed similar proportion of functional independence at 90 days (OR, 1.14; 95% CI, 0.926-1.397; P = 0.219; I2 =36.2%, P = 0.128) compared to those treated with delayed EVT. Delayed EVT was also associated with no significant difference in rates of mortality (OR, 1.015; 95% CI, 0.852 - 1.209; P = 0.871; I2 =0.0%, P = 0.527), successful recanalization (OR, 1.255; 95% CI, 0.923 - 1.705; P = 0.147; I2 =60.5%, P = 0.009) and sICH (OR, 0.976; 95% CI, 0.737 - 1.293; P = 0.871; I2 =0.0%, P = 0.742) compared with early EVT. Conclusions: Among correctly selected AIS patients, delayed EVT showed comparable outcomes in rates of functional independence, recanalization, mortality, and sICH compared with early EVT.